Description Of Poly(aryl-ether-ketone) Materials (paeks),Polyetheretherketone (peek) And Polyetherketoneketone (pekk) For Application As A Dental Material: A Materials Science Review - Syazwani Mohamad Zol; Muhammad Syafiq Alauddin; Zulfahmi Said; Mohd Ifwat Mohd Ghazali; Lee Hao-Ern; Durratul Aqwa Mohd Farid; Nur A’fifah Husna Zahari; Aws Hashim Ali Al-Khadim; Azrul Hafiz Abdul Aziz (MDPI, 2024)
Indexed by WOS/Scopus/ERA